Transformasi praktik akuntansi Usaha Mikro, Kecil, Menengah (UMKM): dari memori ke catatan - Dian Syariati; Unti Ludigdo; Ali Djamhuri (Universitas Negeri Malang, 2020)
Research on the accounting practices of micro, small and medium enterprises (SMEs) in Indonesia shows the failed implementation of accounting standards by SMEs. Since accounting practice is determined by internal and external factors that surround it and small firm is a unique entity, this research finding is interesting to be studied further by understanding accounting practiced by SMEs. Accounting may practice in the other form that further explains the